Coupling of Iron Assimilation and Pectinolysis in Erwinia chrysanthemi 3937 - Franza, Thierry; Michaud-Soret, Isabelle; Piquerel, Pierrette; Expert, Dominique (Molecular plant-microbe interactions, 2002)
Two major virulence determinants of the plant-pathogenic enterobacterium Erwinia chrysanthemi strain 3937 are the production of pectate lyase enzymes that degrade plant cell walls and expression of two high-affinity iron uptake systems mediated by two structurally unrelated siderophores, chrysobactin and achromobactin. Low iron availability is a signal that triggers transcription of the genes encoding pectate lyases PelD and PelE as well as that of genes involved in iron transport. This metalloregulation is mediated by the transcriptional repressor Fur. In this study, we analyzed the molecular mechanisms of this control. We purified the Erwinia chrysanthemi Fur protein. Band shift assays showed that Fur specifically binds in vitro to the regulatory regions of the genes encoding the ferrichrysobactin outer membrane receptor Fct and the pectate lyases PelD and PelE. We identified the Fur-binding sites of these promoter regions by performing DNase I footprinting experiments. From these data, we propose that Fur could inhibit the activation of the pelD and pelE genes by the cAMP receptor protein CRP according to an anti-activation mechanism. To identify other possible effectors involved in this control, we screened a bank of insertion mutants for an increase in transcriptional activity of pelD and fct genes in response to iron limitation. We isolated a mutant affected in the kdgK gene encoding the 2-keto-3-deoxygluconate (KDG) kinase, an enzyme involved in pectin catabolism. The growth of this mutant in the presence of pectic compounds led to a constitutive expression of iron transport genes as well as complete derepression of the pectinolysis genes. This effect was caused by intracellular accumulation of KDG. However, the derepression of iron transport genes by KDG does not involve the KdgR regulator of pectinolysis genes, which uses KDG as inducer. Thus, in Erwinia chrysanthemi, iron depletion or presence of KDG induces transcription of the genes involved in iron assimilation and pectinolysis. These important pathogenicity functions are coregulated by responding to common signals encountered in planta.